Analisis Rancang Bangun Aplikasi Morning Activity Tahfidz dan Tilawah Siswa menggunakan Prototype - Shudiq, Wali Ja'far; Arifin, Zainal; Rizqi Minallah, Moh. Januar; Syaikhu, Rio Ahmad; Wafi, Abd (TRILOGI: Jurnal Ilmu Teknologi, Kesehatan, dan Humaniora, 2025)
Tahfidz and tilawah activities play a significant role in shaping the religious character of students, particularly in Islamic-based educational institutions. However, these activities are often not well-documented or systematically monitored. This study aims to analyze and design a Morning Activity application to support the digital recording and monitoring of students' tahfidz and tilawah activities. The research employs the Prototype development model, which allows iterative system development based on user feedback. The application is designed using both web and mobile-based platforms to ensure accessibility for students and supervising teachers. The result of this study is a prototype application featuring daily input of tilawah, memorization achievements, reminder notifications, and student progress reports. Preliminary testing shows that the application enhances student engagement and facilitates easier monitoring for teachers. Therefore, the implementation of this application is expected to improve the effectiveness of tahfidz and tilawah programs in schools.